Organische Nanopartikel zum Aufbau photoaktiver Schichten Organischer Solarzellen - Gärtner, Stefan (KIT Scientific Publishing, 2017)
Nanoparticle dispersions were used to fabricate photoactive layers of organic solar cells from water or ethanol. By using a precipitation method the power conversion efficiencies of the nanoparticulate solar cells were similar to the ones obtained from the respective solution processed counter parts using a chlorinated solvent. Next to the thoroughly investigated material system P3HT:ICBA also the transfer to other material systems was examined.